Attitude and use of herbal medicines among pregnant women in Nigeria (2009)
Background: The use of herbal medicines among pregnant women in Nigeria has not been widely studied. Methods: Opinion of 595 pregnant women in three geopolitical zones in Nigeria on the use of herbal medicines, safety on usage, knowledge of potential effects of herbal remedies on the fetus and potential benefits or harms that may be derived from combining herbal remedies with conventional therapies were obtained using a structured questionnaire between September 2007 and March 2008. Descriptive statistics and Fisher's exact tests were used at 95% confidence level to evaluate the data obtained. Level of significance was set at p < 0.05. Results: More than two-third of respondents [67.5%] had used herbal medicines in crude forms or as pharmaceutical prepackaged dosage forms, with 74.3% preferring self-prepared formulations. Almost 30% who were using herbal medicine at the time of the study believed that the use of herbal medicines during pregnancy is safe. Respondents' reasons for taking herbal medications were varied and included reasons such as herbs having better efficacy than conventional medicines [22.4%], herbs being natural, are safer to use during pregnancy than conventional medicines [21.1%], low efficacy of conventional medicines [19.7%], easier access to herbal medicines [11.2%], traditional and cultural belief in herbal medicines to cure many illnesses [12.5%], and comparatively low cost of herbal medicines [5.9%]. Over half the respondents, 56.6% did not support combining herbal medicines with conventional drugs to forestall drug-herb interaction. About 33.4% respondents believed herbal medicines possess no adverse effects while 181 [30.4%] were of the opinion that adverse/side effects of some herbal medicines could be dangerous. Marital status, geopolitical zones, and educational qualification of respondents had statistically significant effects on respondents views on side effects of herbal medicines [p < 0.05)] while only geopolitical zones and educational qualifications seemed to have influence on respondents' opinion on the harmful effects of herbal medicines to the fetus [p < 0.05]. Conclusion: The study emphasized the wide spread use of herbal medicines by pregnant women in Nigeria highlighting an urgent need for health care practitioners and other health care givers to be aware of this practice and make efforts in obtaining information about herb use during ante-natal care. This will help forestall possible interaction between herbal and conventional medicines.